2017
DOI: 10.1093/cercor/bhx194
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Responses to Alien Odors in Newborns: An fNIRS Study

Abstract: Very preterm (VPT) infants are exposed to odors released by healthcare products, triggering the trigeminal and olfactory subsystems. Irritation of the nasal mucosa induces pain in adults. We examined whether preterm and full-term (FT) newborns perceived trigeminal odors at different cortical levels, whether these odors elicit pain, and if oral glucose modulates this pain. We performed 44 recording sessions in newborn (15 VPT infants, 12 VPT infants at term-equivalent age, and 17 FT infants) following exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 63 publications
1
43
0
10
Order By: Relevance
“…One study investigated newborns with HIE alongside a control group (Chen et al, 2002 ); only the results from the control group are presented here. Similarly, some studies looked at both term and preterm newborns (Isobe et al, 2001 ; Ozawa et al, 2011a ; Naoi et al, 2013 ; Carlier-Torres et al, 2014 ; Frie et al, 2017 ; Arimitsu et al, 2018 ) or included subjects older than 30 days (Meek et al, 1998 ); the results presented here only include the responses from the term infants <30 days old.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study investigated newborns with HIE alongside a control group (Chen et al, 2002 ); only the results from the control group are presented here. Similarly, some studies looked at both term and preterm newborns (Isobe et al, 2001 ; Ozawa et al, 2011a ; Naoi et al, 2013 ; Carlier-Torres et al, 2014 ; Frie et al, 2017 ; Arimitsu et al, 2018 ) or included subjects older than 30 days (Meek et al, 1998 ); the results presented here only include the responses from the term infants <30 days old.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies used an olfactory stimulus in newborns. All studies monitored the frontal lobe with one study additionally monitoring the parietal lobe (Frie et al, 2017 ). All three studies found a positive response of Δ[HbO 2 ] with results of Δ[HHb] not being reported in two studies (Barton, 2000 ; Aoyama et al, 2010 ) and showing a negative response in one study (Frie et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bright light invokes physiologic dysregulation in NICU infants and can contribute to poor visual development (Watanabe et al, 2013). Finally, noxious smells from disinfectants, adhesives, lubricants, skin care products, and hand hygiene products induce pain responses in NICU infants (Frie, Bartocci, Lagercrantz, & Kuhn, 2017;Kuhn, Astruc, Messer, & Marlier, 2011;Lipchock, Reed, & Mennella, 2011).…”
Section: Nature Of Stressorsmentioning
confidence: 99%
“…Smell is processed in the orbitofrontal cortex, which has been demonstrated with near‐infrared spectroscopy. Pleasant smells like vanilla and colostrum have been shown to evoke increased hemodynamic responses, unlike unpleasant smells like disinfectant or detergent …”
Section: The Infantmentioning
confidence: 99%